VALMIKI'S RAMAYANA REVISITED: WORSHIP BY CONFRONTATION: VIDVESHA-BHAKTI: . - Amodio, Barbara A. (Journal of Dharma, 1991)
The great Adikavi Valmiki, the inspired rishi of India's classic epic, the Ramayana, is the master storyteller of the famous tale of Rama come to deliver the world from Ravana, Lord of the Rakshasas.1 So compelling is the tale that it has grounded no less than nine wellknown Ramayanas each of which assumes a particular angle of vision and an esoteric emphasis of its own based on the richness of Valmiki's original.2 Valmlki himself later composed the Maharamayana or Yoga Vaslstha, a long metaphysical classic that assumes an authoritative rOle in the Indian tradition exploiting as it does the inner development of Rama as the Seventh lncernatlon of Vishnu